The Effect of Long Storage of Temperature Refrigerator to The Eksternal and Internal Quality of Herbal Egg Layer Second Phase - Syahrio Tantalo; Sri Suharyati (JURNAL ILMIAH PETERNAKAN TERPADU, 2022)
This study aimed to determine the effect of storage time at refrigerator temperature on the external and internal quality of the second phase layer chicken herbal eggs. This research was conducted on May 21 – September 2021 at the Livestock Production Laboratory, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. This research was conducted experimentally using a completely randomized design (CRD) consisting of 9 treatments and 4 replications. Each replication consisted of 3 eggs. The data obtained were analyzed for Analysis of Variance at the 5% level of significance, the results of the variance analysis were significantly different, the Least Significant Difference test was continued. The results of this study showed that the weight of herbal eggs decreased significantly (P<0.05) with increasing storage time, which was for 8 weeks ranging from 0.90% – 5.82%. Albumen index also decreased and the storage of herbal eggs for 0 weeks (0.073) was significantly (P<0.05) higher than storage for 1-8 weeks (0.061-0.036). Likewise, the yolk index in herbal egg storage for 0 – 1 week (0.420 – 0.411) was significantly higher (P<0.05) compared to storage for 2 – 8 weeks (0.388 – 0.358). On the other hand, the size of the air cavity diameter showed that the longer the storage time is increasing, which is for 8 weeks ranging from 1.409 cm – 3.058 cm. The quality of the second phase layer chicken herbal eggs was classified as well based on the average HU value (52.25 – 72.55). Conclusion of this study were 1) the longer storage time at refrigerator temperature could decrease egg weight, albumen index, yolk index, air cavity diameter, and Haugh Unit and could increase the size of the air cavity diameter of second phase layer chicken herbal eggs; and 2) the quality of the second phase layer chicken herbal eggs that were stored at refrigerator temperature for up to 8 weeks was classified as well based on the average HU value